Transition from paediatric to adult health services in Scotland for young people with cerebral palsy. (June 2016) - Wright, Alice E; Robb, James; Shearer, Morven C
Transition from paediatric to adult health-care services has been characterized as being poorly planned and coordinated, resulting in a reduction in services and may be distressing for families. This study aimed to establish what provisions are currently available in Scotland for transition of young people with cerebral palsy and what some clinicians believe future provisions should involve. Semi-structured interviews were conducted with 13 community paediatricians (or equivalents in health boards without community paediatricians) from 12 different Scottish health boards. Interviews were audio recorded, transcribed and analysed thematically using framework analysis. Both current transition provision and the areas that the clinicians felt needed improvement varied greatly between health boards. Key areas in need of improvement were coordination and communication within health services and also between health services and educational, social services and adult health services to which young people were transitioning. Transition remains problematic and variable. For transition to be improved, further research is needed to explore the effect this variation is having on young people and their families.